Social Changes of Traditional Rules in Facing Contemporary Developments: A Sociological Study of Intercaste Marriagein Balinese Society - Sadnyini, Ida Ayu; Gorda, A.A.A. Ngurah Tini Rusmini (International Journal of Criminology and Sociology, 2021)
Nowadays, it is important to examine the impetus for changes of traditional rules in facing contemporary developments and in this regard, this study took a private subject of rules on inter-caste marriage in the Balinese Hindu community. In this context, this study aims to investigate how the inter-caste marriage system is run as an effort to bridge traditional values and modern values based on legal equality and citizenship by taking Balinese society. This research is empirical research with a historical approach with the object of the research is inter-caste marriages. The results showed that the development of inter-caste marriage rules in the monarchy period was derived from Hindu law. The rules on inter-caste marriage during the colonial period can be found in the Peswara and after the independence, the inter-caste marriage is regulated in the Decree of House of Representative of Bali Province, Bhisama Sabha Pandita, and the Decree of MDP Bali. The Hindu community still maintains the sanctions against inter-caste marriage because of their adherence to the customary law of the traditional village.